Nuclear calcium-VEGFD signaling controls maintenance of dendrite arborization necessary for memory formation - Mauceri, Daniela; Freitag, H. Eckehard; Oliveira, Ana; Bengtson, C. Peter; Bading, Hilmar (Neuron, 2011)
The role of neuronal dendrites is to receive and process synaptic inputs. The geometry of the dendritic arbor can undergo neuronal activity-dependent changes that may impact the cognitive abilities of the organism. Here we show that vascular endothelial growth factor D (VEGFD), commonly known as an angiogenic mitogen, controls the total length and complexity of dendrites both in cultured hippocampal neurons and in the adult mouse hippocampus. VEGFD expression is dependent upon basal neuronal activity and requires nuclear calcium-calmodulin-dependent protein kinase IV (CaMKIV) signaling. Suppression of VEGFD expression in the mouse hippocampus by RNA interference causes memory impairments. Thus, nuclear calcium-VEGFD signaling mediates the effect of neuronal activity on the maintenance of dendritic arbors in the adult hippocampus and is required for cognitive functioning. These results suggest that caution be employed in the clinical use of blockers of VEGFD signaling for antiangiogenic cancer therapy.